Zakat for Infrastructure: A Contextual Analysis of Verse 60 of Surah Al-Taubah in the Commentaries of Al-Qurtubi and Al-Razi - Khairussalam Khairussalam; Masrukhin Muhsin; Hafidz Taqiyuddin (al-Afkar, Journal For Islamic Studies, 2026)
This study investigates the discourse around the allocation of zakat funds for the enhancement of public infrastructure, including educational institutions, healthcare facilities, and transportation networks, which stems from divergent interpretations of the term fi sabilillah in the Quranic verse. “Surah At-Taubah, verse 60. Al-Qurtubi understood the phrase as strictly pertaining to jihad, whilst al-Razi had a broader interpretation encompassing diverse sorts of public welfare. This study aims to examine the divergent perspectives of the two commentators and evaluate the legitimacy of utilizing zakat monies for infrastructure in accordance with the principle of maqasid al-shariah. This study employs a qualitative methodology utilizing a literature review approach to assess the writings of both commentators descriptively and comparably. The findings indicate that al-Qurtubi restricts the application of zakat to physical jihad, but al-Razi offers a more expansive view for the public good. Utilizing the maqasid al-shariah framework, infrastructure development may be classified as fi sabilillah, provided it adheres to the principle of benefit and aligns with sharia regulations. This research affirms that the comprehension of zakat can be adapted to contemporary exigencies.